PENGARUH PERSEPSI KERJA DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN SEKOLAH TINGGI PARIWISATA AMPTA YOGYAKARTA DENGAN KOMPENSASI KERJA SEBAGAI VARIABLE MODERASI. - Parsidi, Parsidi; Hendrajaya, Soetomo WE (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2015)
The title of this research is The Influence of Work Perception and Work Motivation on the Lecturers’s Performances in Sekolah Tinggi Pariwisata AMPTA Yogyakarta with Compensation as the moderating variable.This research aims to investigate the influence of Work Perception, Work Motivation on the Lecturers’ performances in Sekolah Tinggi Pariwisata AMPTA Yogyakarta with Compensation as the moderating variable. The research was an Inferential Quantitative. The sample consist of 39 persons who were permanent Lecturers in Sekolah Tinggi Pariwisata AMPTA. The sample was established by applying Census sampling method because the respondent were less than 100 persons. The data were collected by using questionnaire. The data were tested and analyzed by applying multiple linear regression. The analysis results indicated that (1) work perception positively influencing and significant to the lecturers performances, (2) work motivation positively influencing and significant to the lecturers’ performances, (3) work compensation positively influencing and significant to the lecturer’ performance, (4) work perception positively influencing and significant to the lecturers’ performance with work compensation as moderating variable, and (5) work motivation positively influencing and significant to the lecturers’performance with work compensation as moderating variable. Keywords: Work perception, Work motivation, Lecturers’performances, work Compensation.